RELATED CHANGES OF SERUM CYTOKINES AND MARKERS OF THE SECRETORY ACTIVITY OF THE GASTRIC MUCOSA AT ULCEROUS PROCESS - L. V. Matveeva; M. A. Stenina; L. M. Mosina (Медицинская иммунология, 2014)
Abstract. The aim of the study was to determine the concentrations of cytokines and pepsinogen in identifying the presence and strength of them relationship with acute gastric ulcer. ELISA method in the serum of the subjects were evaluated levels pro- and antiinflammatory cytokines and pepsinоgenes. Found a number of statistically significant, pathogenetic correla-tions that can be recommended for the combined determination of the immunodiagnostics and individual correction therapy.